2015
DOI: 10.1186/s12937-015-0038-8
|View full text |Cite
|
Sign up to set email alerts
|

Zingiberaceae extracts for pain: a systematic review and meta-analysis

Abstract: BackgroundMembers of the family Zingiberaceae including turmeric, ginger, Javanese ginger, and galangal have been used for centuries in traditional medicine. Preclinical studies of Zingiberaceae extracts have shown analgesic properties. This study aims to systematically review and meta-analyze whether extracts from Zingiberaceae are clinically effective hypoalgesic agents.MethodsLiterature was screened from electronic databases using the key words Zingiberaceae AND pain OR visual analogue score (VAS) to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
55
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 68 publications
5
55
0
5
Order By: Relevance
“…8,9 They have been used as seasonings in many ethnic cuisines in various countries such as Bangladesh, India, and Pakistan. They have long been used as anti-inflammatory treatments in traditional Chinese and Ayurvedic medicines.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 They have been used as seasonings in many ethnic cuisines in various countries such as Bangladesh, India, and Pakistan. They have long been used as anti-inflammatory treatments in traditional Chinese and Ayurvedic medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms of action include modulation of leukotriene (LT) and prostaglandin (PG) synthesis and inhibition of nuclear factor-κB (11). In vitro , the main components of ginger (gingerols and shogaols) can inhibit the synthesis of several pro-inflammatory cytokines including IL-1, tumour necrosis factor (TNF)-α, and IL-8 as well as PG and LT synthesis enzymes (6, 12).…”
mentioning
confidence: 99%
“…Shokyo is the powdered rhizome of ginger (Zingiber offinale Roscoe), whereas, kankyo is the steamed and powdered rhizome of ginger. Many reports demonstrated that ginger has anti-inflammatory effects in human (Afzal et al, 2001;Lakhan et al, 2015), animal (Thomson et al, 2002;Aimbire et al, 2007;El-Abhar et al, 2008), and in vitro models (Ara and Sogawa, 2016;Podlogar and Verspohl, 2012). Shokyo contains gingerols such as 6-, 8-, and 10-gingerols.…”
Section: Discussionmentioning
confidence: 99%